If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.3(t + -2) = 0.4t Reorder the terms: 0.3(-2 + t) = 0.4t (-2 * 0.3 + t * 0.3) = 0.4t (-0.6 + 0.3t) = 0.4t Solving -0.6 + 0.3t = 0.4t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-0.4t' to each side of the equation. -0.6 + 0.3t + -0.4t = 0.4t + -0.4t Combine like terms: 0.3t + -0.4t = -0.1t -0.6 + -0.1t = 0.4t + -0.4t Combine like terms: 0.4t + -0.4t = 0.0 -0.6 + -0.1t = 0.0 Add '0.6' to each side of the equation. -0.6 + 0.6 + -0.1t = 0.0 + 0.6 Combine like terms: -0.6 + 0.6 = 0.0 0.0 + -0.1t = 0.0 + 0.6 -0.1t = 0.0 + 0.6 Combine like terms: 0.0 + 0.6 = 0.6 -0.1t = 0.6 Divide each side by '-0.1'. t = -6 Simplifying t = -6
| 9-81=10x-x | | 18-5p=-4(5+6p) | | 6(c+4)=4c+-18 | | -17=17x | | 8x-(6x-2)=-2 | | -n=-6 | | 135n+500=35(n+5) | | 3(2t-5)=30-3t | | 256=x^4 | | 36x^2-144x+6=0 | | 8+8x+25-5x=9 | | 7x-26x=38 | | 2x^2-16x=66 | | c=2xr | | 7x+8+11=7 | | 17.50x+185+220=842.50 | | 3(2k-2)=-2(4k-11) | | 1512/4000000= | | 30-7x=10z-4 | | u+7=9 | | x+3-2x=23 | | -c=-12 | | 15=5-2Q | | 36-2x=-x+4 | | 5y-4=9y+8 | | y=5mx-2b | | 4/1=z/16 | | 10x+4=2(5x+2) | | c=2.03*2+14.37 | | 3.7a+4.4=-40 | | 3.9r= | | 50t-2=2t+34 |